Pola Pewarisan Kaki Rengket Secara Autosomal Resesif dan Koefisien Inbreeding pada Ayam Pelung di Cianjur (THE AUTOSOMAL RECESSIVE IN CROOPER TOES INHERRITANCE PATTERN AND INBREEDING COEFFICIENT IN PELUNG CHICKEN AT CIANJUR) - Daryono, Budi Setiadi; Mushlih, Miftahul (Jurnal Veteriner; Vol 17 No 2 (2016), 2016)
Pelung Chicken is classified as dual-purpose chicken (meat and singer). Physical abnormalities affectthe selling price. One of the common physical abnormalities is crooked toes. The aims of this study were todeterminate the crooked toes inheritance pattern and the value of inbreeding coefficient (IC) in Pelungchicken. The method that used in this study is descriptive-explorative and samples were taken usingpurposive sampling analysis. The research was conducted at Cibeber, Cianjur district, West Java.inbreeding coeficient was determined using F = “ (1/2)n+1 (1+Fc) formula and inheritance pattern wasdetermined by the pedigree resulted and chi-square test goodness of fit test. The results show that aCreeper abnormality is inherited as autosomal recessive with the IC value reaches 0.6. The highest valueof IC shows highest risk probability of crooked toes in pelung chicken.
Keywords: pelung chicken, crooked toes, inherritance pattern, inbreeding coeffsient